2020
DOI: 10.1200/go.20.00145
|View full text |Cite
|
Sign up to set email alerts
|

Poor Biological Factors and Prognosis of Interval Breast Cancers: Long-Term Results of Bahçeşehir (Istanbul) Breast Cancer Screening Project in Turkey

Abstract: PURPOSE The Turkish Bahçeşehir Breast Cancer Screening Project was a 10-year, organized, population-based screening program carried out in Bahçeşehir county, Istanbul. Our aim was to examine the biologic features and outcome of screen-detected and interval breast cancers during the 10-year study period. METHODS Between 2009 and 2019, 2-view mammograms were obtained at 2-year intervals for women aged 40 to 69 years. Clinicopathological characteristics including ER, PR, HER2-neu, and Ki-67 status were analyzed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 38 publications
(46 reference statements)
0
5
0
1
Order By: Relevance
“…Comparative data on the distribution of Ki-67 in interval carcinomas have been sparse. In a paper by Cabioglu published in 2020, the proportion of interval carcinomas with high Ki-67 expression (≥ 20 %) was nearly twice as high as in tumors detected by screening [31].…”
Section: Ki-67 Proliferation Markermentioning
confidence: 97%
See 1 more Smart Citation
“…Comparative data on the distribution of Ki-67 in interval carcinomas have been sparse. In a paper by Cabioglu published in 2020, the proportion of interval carcinomas with high Ki-67 expression (≥ 20 %) was nearly twice as high as in tumors detected by screening [31].…”
Section: Ki-67 Proliferation Markermentioning
confidence: 97%
“…Vergleichsdaten zur Verteilung von Ki-67 bei Intervallkarzinomen gibt es bisher nur vereinzelt. In einer 2020 veröffentlichten Arbeit von Cabioglu war der Anteil mit hoher Ki-67-Expression (≥ 20 %) bei den Intervallkarzinomen ebenfalls fast doppelt so hoch wie bei im Screening detektierten Tumoren [31].…”
Section: Proliferationsmarker Ki-67unclassified
“…[5] In Türkiye it has been demonstrated that identifying women at risk of breast cancer and providing their regular involvement in cancer screening can reduce their morbidity and mortality from breast cancer. [6] The American College of Radiology (ACR) and the Society of Breast Imaging recommend annual screening mammography by the age of 40. [7][8][9] Research conducted in Türkiye demonstrates that breast cancer screening programs are not used enough.…”
Section: Introductionmentioning
confidence: 99%
“…Even though early detection and screening services are available and free of charge within the national cancer screening program, women's participation in breast cancer screening is extremely low. [3,6,[9][10][11][12] The aim of this study was to examine the awareness and comprehension of breast cancer, the screening program, and mammography among female academic staff members who work in an academic study center, as well as female patients who applied to the general surgery outpatient clinic with complaints unrelated to breast.…”
Section: Introductionmentioning
confidence: 99%
“…Breast cancer is reported to the most frequent cancer suffered by women in Turkey (Cebeci, Balcı Yangın & Tekeli, 2012;Cabioğlu et al, 2020;Selçuk et al, 2020) as it accounts for approximately one in four cancers in the world (Karadeniz Çakmak et al, 2020). Breast cancer is also known as the leading cause of cancer death among women (Unger-Saldana, 2014) with nearly 656,000 deaths in 2020 in the world (WHO, 2020).…”
Section: Introductionmentioning
confidence: 99%